2013
DOI: 10.1089/cyber.2012.0157
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality as a Mediator Between Technology-Related Sleep Quality, Depression, and Anxiety

Abstract: This study examines (a) relations among technology use during sleep time, sleep quality, and depression/anxiety and (b) time awake due to technology use. Two hundred thirty-six college students completed self-report questionnaires and week-long sleep diaries. Results revealed that 47 percent of students reported night-time waking to answer text messages and 40 percent to answer phone calls. Regression analyses indicated that higher levels of technology use after the onset of sleep predicted poorer sleep qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 31 publications
(35 reference statements)
2
93
2
3
Order By: Relevance
“…18 Moreover, Adams et al reported that depressed individuals might have sleep problems and use the technology to pass the time this could be plausible reason for our findings on depression, stress and anxiety. 19 Lemola et al found that electronic media use at night is related to sleep disturbances and depressive symptoms which is similar to findings of present study. 15 The researchers reported that electronic media use at night was associated with depressive symptoms.…”
Section: -11supporting
confidence: 91%
“…18 Moreover, Adams et al reported that depressed individuals might have sleep problems and use the technology to pass the time this could be plausible reason for our findings on depression, stress and anxiety. 19 Lemola et al found that electronic media use at night is related to sleep disturbances and depressive symptoms which is similar to findings of present study. 15 The researchers reported that electronic media use at night was associated with depressive symptoms.…”
Section: -11supporting
confidence: 91%
“…Furthermore, also Brunborg et al (2011) controlled for depressive symptoms when assessing the relationship between using the mobile phone in the bedroom at night and sleep disturbance in young adults. A formal test of the mediation hypothesis that sleep disturbance may mediate the relationship between electronic media use and depressive symptoms was conducted by two studies (Adams and Kisler 2013;Lemola et al 2011). Results from Adams and Kisler (2013) support the mediation hypothesis in a sample of college students.…”
Section: The Role Of Sleep Disturbance For the Relationship Between Ementioning
confidence: 90%
“…A formal test of the mediation hypothesis that sleep disturbance may mediate the relationship between electronic media use and depressive symptoms was conducted by two studies (Adams and Kisler 2013;Lemola et al 2011). Results from Adams and Kisler (2013) support the mediation hypothesis in a sample of college students. In contrast, Lemola et al (2011) could not find mediation of the relationship between habitual video game playing at night and depressive symptoms by sleep disturbance in a sample of adolescents and young adults who played the online multiplayer role play game World of Warcraft.…”
Section: The Role Of Sleep Disturbance For the Relationship Between Ementioning
confidence: 90%
“…Esto se debe en su mayoría, a que el celular es un recurso que suele estar siempre presente, acvo y a disposición de las personas; por ende, interfiere constantemente en la interacción de la pareja (Jarvenpaa & Lang, 2005). A su vez, varias inves gaciones han encontrado correlaciones posi vas entre un alto uso de la tecnología, los disposi vos electrónicos y la depresión (Adams & Kisler, 2013;Gen le et al, 2011;Pan c et al, 2012). Por estas razones, argumentamos que el phubbing en la pareja tendrá un efecto indirecto en el bienestar psicológico y la salud mental de los individuos, a través de la sa sfacción en la relación de pareja.…”
Section: Phubbing Y Relaciones Román Casunclassified